Single Cell Analysis of Endothelial Cells Identified Organ-Specific Molecular Signatures and Heart-Specific Cell Populations and Molecular Features - Feng, Wei; Chen, Lyuqin; Nguyen, Patricia K.; Wu, Sean M.; Li, Guang (Frontiers in Cardiovascular Medicine, 2019)
Endothelial cells line the inner surface of vasculature and play an important role in normal physiology and disease progression. Although most tissue is known to have a heterogeneous population of endothelial cells, transcriptional differences in organ specific endothelial cells have not been systematically analyzed at the single cell level. The Tabula Muris project profiled mouse single cells from 20 organs. We found 10 of the organs profiled by this Consortium have endothelial cells. Unsupervised analysis of these endothelial cells revealed that they were mainly grouped by organs, and organ-specific cells were further partially correlated by germ layers. Unexpectedly, we found all lymphatic endothelial cells grouped together regardless of their resident organs. To further understand the cellular heterogeneity in organ-specific endothelial cells, we used the heart as an example. As a pump of the circulation system, the heart has multiple types of endothelial cells. Detailed analysis of these cells identified an endocardial endothelial cell population, a coronary vascular endothelial cell population, and an aorta-specific cell population. Through integrated analysis of the single cell data from another two studies analyzing the aorta, we identified conserved cell populations and molecular markers across the datasets. In summary, by reanalyzing the existing endothelial cell single-cell data, we identified organ-specific molecular signatures and heart-specific subpopulations and molecular markers. We expect these findings will pave the way for a deeper understanding of vascular biology and endothelial cell-related diseases.